Suitability of selected legume (Vachellia spp.) tree species for forest restoration in the Central Ethiopian highlands - ASMELASH, FISSEHA; GETACHEW, EMEBET (Nusantara Bioscience, 2022)
Abstract. Asmelash F, Getachew E. 2022. Suitability of selected legume (Vachellia spp.) tree species for forest restoration in the Central Ethiopian highlands. Nusantara Bioscience 14: 195-202. This study aimed to evaluate the comparative suitability of the legume tree species viz., Vachellia abyssinica (Hochst. ex. Benth.) Kyal. & Boatwr., Vachellia etbaica (Schweinf.) Kyal. & Boatwr., Vachellia lahai (Steud. & Hochst. ex Benth.) Kyal. & Boatwr., and Vachellia seyal (Delile) P.J.H.Hurter for restoring forests in Central Ethiopian highlands. The suitability of three accessions of V. seyal was also compared. The correlation between root nodule number and root Arbuscular Mycorrhizal Fungi (AMF) colonization (RC) and seedlings’ growth variables were computed, and the effect of seedling age on nodule number and RC was determined. Seedlings were grown for nine months on degraded local soil in a mesh house in central Ethiopia. We measured shoot height, shoot fresh weight, rooting depth, root nodule number, and RC in the third and ninth months. The one-way ANOVA results indicated that tree species and/or accession (for V. seyal) had a significant (p
Keywords: Arbuscular mycorrhizal fungi, nitrogen fixation, nodulation, rhizobium, Vachellia etbaica